Oblique Wave Scattering by a Vertical Flexible Porous Plate. Issue 1 (12th February 2015) - Koley, S.; Kaligatla, R. B.; Sahoo, T.
<x xml:space="preserve">Abstract</x> In the present study, oblique surface wave scattering by a submerged vertical flexible porous plate is investigated in both the cases of water of finite and infinite depths. Using Green's function technique, the boundary value problem is converted into a system of three Fredholm type integral equations. Various integrals associated with the integral equations are evaluated using appropriate Gauss quadrature formulae and the system of integral equations are converted into a system of algebraic equations. Further, using Green's second identity, expressions for the reflection and transmission coefficients are obtained in terms of the velocity potential and its normal derivative. Energy balance relations for wave scattering by flexible porous plates and permeable membrane barriers are derived using Green's identity and used to check the correctness of the computational results. From the general formulation of the submerged plate, wave scattering by partial plates such as (i) surface‐piercing and (ii) bottom‐standing plates are studied as special cases. Further, oblique wave scattering by bottom‐standing and surface‐piercing porous membrane barriers are studied in finite water depth as particular cases of the flexible plate problem. Various numerical results are presented to study the effect of structural rigidity, angle of incidence, membrane tension, structural length, porosity and water depth on wave scattering. It is found that wave reflection is more for a surface‐piercing flexible porous plate in infinite water depth compared to finite water depth and opposite trend is observed for a submerged flexible porous plate. For a surface‐piercing nonpermeable membrane, zeros in transmission coefficient are observed for waves of intermediate water depth which disappear with the inclusion of porosity. The study reveals that porosity has small influence on the wave‐induced excitation of the structure with higher flexibility but it tends to reduce the deflection of a stiffer structure. In case of partial flexible plates and membrane barriers, irrespective of the gap length, full transmission occurs due to wave diffraction through the gap in the very long wave regime while, full reflection occurs by complete flexible impermeable barriers for similar wave condition.